Non-steroidal anti-inflammatory drugs, intravenous fluids, pancreatic stents, or their combinations for the prevention of post-endoscopic retrograde cholangiopancreatography pancreatitis: a systematic review and network meta-analysis. (September 2021) - Akshintala, Venkata S; Sperna Weiland, Christina J; Bhullar, Furqan A; Kamal, Ayesha; Kanthasamy, Kavin; Kuo, Albert; Tomasetti, Cristian; Gurakar, Merve; Drenth, Joost P H; Yadav, Dhiraj; Elmunzer, B Joseph; Reddy, D Nageshwar; et al.
Summary: Background: Non-steroidal anti-inflammatory drugs (NSAIDs), intravenous fluid, pancreatic stents, or combinations of these have been evaluated in randomised controlled trials (RCTs) for the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis, but the comparative efficacy of these treatments remains unclear. Our aim was to do an exploratory network meta-analysis of previous RCTs to systematically compare the direct and indirect evidence and rank NSAIDs, intravenous fluids, pancreatic stents, or combinations of these to determine the most efficacious method of prophylaxis for post-ERCP pancreatitis. Methods: We searched PubMed, Embase, and the Cochrane Central Register from inception to Nov 15, 2020, for full-text RCTs that evaluated the efficacy of NSAIDs, pancreatic stents, intravenous fluids, or combinations of these for post-ERCP pancreatitis prevention in adult (aged ≥18 years) patients undergoing ERCP. Summary data from intention-to-treat analyses were extracted from published reports. We analysed incidence of post-ERCP pancreatitis across studies using network meta-analysis under the frequentist framework, obtaining pairwise odds ratios (ORs) and 95% CIs. We used the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system for the confidence rating. This study is registered with PROSPERO, CRD42020172606. Findings: We identified 1503 studies, of which 55 RCTs evaluating 20 interventions in 17 062 patients were included in the network meta-analysis. The mean incidence of post-ERCP pancreatitis in the placebo or active control group was 12·2% (95% CI 11·4–13·0). Normal saline plus rectal indometacin (OR 0·02, 95% CI 0·00–0·40), intramuscular diclofenac 75 mg (0·24, 0·09–0·69), intravenous high-volume Ringer's lactate plus rectal diclofenac 100 mg (0·30, 0·16–0·55), intravenous high-volume Ringer's lactate (0·31, 0·12–0·78), 5–7 Fr pancreatic stents (0·35, 0·26–0·48), rectal diclofenac 100 mg (0·36, 0·25–0·52), 3 Fr pancreatic stents (0·47, 0·26–0·87), and rectal indometacin 100 mg (0·60, 0·50–0·73) were all more efficacious than placebo for preventing post-ERCP pancreatitis in pairwise comparisons. 5–7 Fr pancreatic stents (0·59, 0·41–0·84), intravenous high-volume Ringer's lactate plus rectal diclofenac 100 mg (0·49, 0·26–0·94), intravenous standard-volume normal saline plus rectal indometacin 100 mg (0·04, 0·00–0·66), and rectal diclofenac 100 mg (0·59, 0·40–0·89) were more efficacious than rectal indometacin 100 mg. The GRADE confidence rating was low to moderate for 98·3% of the pairwise comparisons. Interpretation: This systematic review and network meta-analysis summarises the available literature on NSAIDs, pancreatic stents, intravenous fluids, or combinations of these for prophylaxis of post-ERCP pancreatitis. Rectal diclofenac 100 mg is the best performing rectal NSAID in this network meta-analysis. Combinations of prophylaxis might be more effective, but there is little evidence. These findings help to establish prophylaxis of post-ERCP pancreatitis for future research and practice, and could reduce costs and increase adoption of prophylaxis. Funding: None.